Corporate Social Responsibility, Intellectual Capital, Komisaris Independen, dan Kinerja Keuangan - Nurmala, Putri; Rahmawati, Fitri; Adiwibowo, Akhmad Sigit (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
This study aims to determine the effect of corporate social responsibility, intellectual capital, and independent commissioners on the financial performance of energy sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The type of research used is the associative quantitative method. The type of data used is secondary data. The sample selection was done by purposive sampling so that a sample of 10 companies was obtained. Data processing uses the statistical program Eviews 10. The results of the t-test show that corporate social responsibility does not affect financial performance, intellectual capital has no effect on financial performance, and independent commissioners harm financial performance. Keywords: Financial Performance; Corporate Social Responsibility; Intellectual Capital; Independent Commissioner